2017
DOI: 10.1016/j.joca.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective activity of N-acetyl phenylalanine glucosamine derivative on knee joint structure and inflammation in a murine model of osteoarthritis

Abstract: NAPA markedly improved the physical structure of articular cartilage while reducing catabolic enzymes, extracellular matrix (ECM) remodeling and IKKα expression, showing to be able to exert a chondroprotective activity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…OA animal models have a distinct molecular pathophysiology that might promote the translation of disease‐modifying OA therapies from preclinical to clinical trials. Among these models, the DMM model has demonstrated to reproduce the changes observed in clinical settings and be more reliable than other surgical techniques, also mimicking OA that occurs in ageing . Additionally, DMM surgery is highly reproducible, induces OA with a slow progression, with moderate to severe lesions and minimal iatrogenic damage .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OA animal models have a distinct molecular pathophysiology that might promote the translation of disease‐modifying OA therapies from preclinical to clinical trials. Among these models, the DMM model has demonstrated to reproduce the changes observed in clinical settings and be more reliable than other surgical techniques, also mimicking OA that occurs in ageing . Additionally, DMM surgery is highly reproducible, induces OA with a slow progression, with moderate to severe lesions and minimal iatrogenic damage .…”
Section: Discussionmentioning
confidence: 99%
“…Among these models, the DMM model has demonstrated to reproduce the changes observed in clinical settings and be more reliable than other surgical techniques, also mimicking OA that occurs in ageing. 15,26,36,37 Additionally, DMM surgery is highly reproducible, induces OA with a slow progression, with moderate to severe lesions and minimal iatrogenic damage. 26,36,37 As observed by Glasson et al, 26 DMM induces an OA whose severity progresses from mild-Àmoderate to moderate-Àsevere, with lesions on the central weight bearing area of the joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Villermoz et al showed that the overexpression of lumican in a mouse cancer model induced the decrease of Cyclin D1 production, increased apoptosis rate and in turn significantly decreased subcutaneous tumor formation in vivo [42]. Previously, we demonstrated that GlcN and glucosamine-derivative NAPA, were able to stimulate extracellular matrix components, among them also the SLRP lumican and collagens [43,44]. Considering that NCPA is a glucosamine-derivative, very similar to NAPA, we can hypothesize that also NCPA induces lumican production, strengthening the effects on cell cycle and apoptosis that we observed.…”
Section: Discussionmentioning
confidence: 96%